Christianity and Local Culture in Late Roman Africa - Brown, Peter (Journal of Roman Studies, 1968)
The task of this paper is, in part, an invidious one: for I shall have to begin by looking a gift-horse in the mouth. I shall have to question a group of opinions that link the rise of Christianity in Africa with a resurgence of the local culture of the area. This resurgence, it is said, explains not only the rapid collapse of Roman rule at the time of the Vandal invasion of 429, but the disappearance of Roman civilisation and of Christianity itself in Africa in the early Middle Ages. Discussion of this suggestion, however, tends to be jeopardised from the start because claims for the honour of being the resurgent local culture of Late Roman Africa have been enthusiastically advanced on behalf of two distinct and mutually-exclusive local cultures, associated with the two native languages—with Punic, on the one hand, and with ‘Libyan’ (which is often described by a convenient if perilous anachronism as ‘Berber’), on the other. What is more, these claims have been advanced by two equally distinct groups of scholars, handling different evidence. The evidence for the survival of Punic—or, so as not to prejudge the issue, of a lingua Punica —is literary: Augustine of Hippo and Procopius are the sole authorities for the period. The evidence for ‘Berber,’ by contrast, is largely confined to the interpretation of Libyan inscriptions and of traces of unchanging habits of worship and craftsmanship allegedly betrayed in the remains of the Christian Churches of Central Numidia.
Keywords: Christianisme – Djebel Nefousa